APTIMA®Trichomonas vaginalis, a transcription-mediated amplification assay for detection of Trichomonas vaginalis in urogenital specimens. (September 2011) - Chapin, Kimberle; Andrea, Sarah
The APTIMA ® Trichomonas vaginalis (APTIMA TV; Gen-Probe Inc.) assay is the only amplification-based assay for T. vaginalis (TV) currently cleared by the US FDA. The assay was cleared in April 2011. APTIMA TV utilizes target capture specimen processing, transcription-mediated amplification and chemiluminescent probe hybridization for the qualitative detection of TV ribosomal RNA. The assay is used for the screening/diagnosis of trichomoniasis in women. Specimen types that can be used include physician-collected endocervical swabs, vaginal swabs, endocervical specimens collected in PreservCyt ® (Thin Prep, Hologic Incorporated, MA, USA) solution and female urine specimens. The APTIMA TV assay has shown superior performance in side-by-side comparisons with other diagnostic methods in all patient populations and specimen types tested. Clinical sensitivity and specificity are >95 and 98%, respectively. The APTIMA TV assay fills a significant void in sexually transmitted infection diagnostics.